2014
DOI: 10.1093/jnci/dju289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Screening and Systemic Adjuvant Therapy on ER-Specific US Breast Cancer Mortality

Abstract: As advances in risk assessment facilitate identification of women with increased risk of ER-negative breast cancer, additional mortality reductions could be realized through more frequent targeted screening, provided these benefits are balanced against screening harms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
128
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 50 publications
0
128
0
1
Order By: Relevance
“…Since our earlier analysis,(1) the models have undergone substantial revision to reflect advances in breast cancer control, including: portrayal of four distinct molecular subtypes based on estrogen receptor (ER) and human epidermal growth factor-2 receptor (HER2) status;(24) current population incidence (32) and competing non-breast cancer mortality; digital screening; and the most current therapies. (33) All models (except Model S) include DCIS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since our earlier analysis,(1) the models have undergone substantial revision to reflect advances in breast cancer control, including: portrayal of four distinct molecular subtypes based on estrogen receptor (ER) and human epidermal growth factor-2 receptor (HER2) status;(24) current population incidence (32) and competing non-breast cancer mortality; digital screening; and the most current therapies. (33) All models (except Model S) include DCIS.…”
Section: Methodsmentioning
confidence: 99%
“…(22,23) Collaboration of several models provides a range of plausible effects and illustrates the impact of differences in model assumptions. (1,7,24)…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Elaborate models that incorporated data from the Surveillance, Epidemiology, and End Results (SEER) Program of the National Cancer Institute on breast cancer incidence, survival, and many other factors indicated that both screening and adjuvant treatment contributed to improvements in mortality, but estimates were uncertain. [21][22][23] Elkin et al 24 studied secular trends in relative breast cancer survival in SEER from 1975 to 1999. By standardizing on tumor size, they showed that a substantial proportion of the improvement was attributable to decreases in tumor size within local and regional stage.…”
Section: Introductionmentioning
confidence: 99%
“…An update that also used ER status attributed 38% to 52% to screening. 23 It is difficult to compare our findings with these estimates of the proportion of improvements in overall US breast cancer mortality attributable to screening, because these models also incorporated information on the changing stage distribution. It is striking, however, how little of the stage-and age-specific improvements in women younger than age 70 years could be explained by changes in tumor size over time (Figs 2 and 3).…”
mentioning
confidence: 97%
“…Although the prognosis of BC has improved in the last 40 years, this progress has not been equally distributed amongst age groups [5][6] [7]. Prognosis is worse especially in the oldest old (above 80) [8] [9], an age group that has seemingly not profited from improvements in treatment standards [10].…”
Section: Introductionmentioning
confidence: 99%